2016
DOI: 10.1371/journal.pone.0145401
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors Influencing Child Health in Ghana

Abstract: ObjectivesSocial factors have profound effects on health. Children are especially vulnerable to social influences, particularly in their early years. Adverse social exposures in childhood can lead to chronic disorders later in life. Here, we sought to identify and evaluate the impact of social factors on child health in Ghana. As Ghana is unlikely to achieve the Millennium Development Goals’ target of reducing child mortality by two-thirds between 1990 and 2015, we deemed it necessary to identify social determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 81 publications
5
43
1
3
Order By: Relevance
“…Numerous previous studies have also reported a significant relationship between maternal education and infant health (27,28). Accordingly, since high maternal education is an important predictor of child health, expanding the health educational programs are required to improve health literacy and health knowledge of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have also reported a significant relationship between maternal education and infant health (27,28). Accordingly, since high maternal education is an important predictor of child health, expanding the health educational programs are required to improve health literacy and health knowledge of mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers who possess high education level will give positive interaction to the process of stimulation on fine motor development of children under five. Maternal education becomes social factor related to the well-being of children's healt (Quansah et al, 2016) F. Frequency of stimulation affected motor development The result of hypothesis showed the existence of positive effect between stimulition frequency with motor development of children under two.…”
Section: A Exclusive Breastfeeding Affectedmentioning
confidence: 97%
“…Inequities in the income distribution imply considerably in the social and health determinants, 1,24,25,26 coming from a social stratification 27 and political inequalities that permeate in the health system and challenges its management. 2 Hence, it is necessary actions that involve the whole political sphere of governments in order to promote social and economic policies capable of reducing income differences and promoting equity in the health system.…”
Section: Variablesmentioning
confidence: 99%